In Memoriam Patrizia Lombardo (1950-2019) - POP-CURȘEU, Ioan (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
Patrizia Lombardo was born in Udine on January 23, 1950. She passed away in Geneva on June 28, 2019. After studying at the University of Venice, Oxford and Princeton, she attended – in Paris – the famous seminars of Roland Barthes, to whom she owed “an attitude, a moral sense”, rather than “a method nor a set of concepts”. She taught at several universities in the United States (Pittsburgh, University of Southern California, Princeton) before settling in Europe at the University of Geneva. She made solid contributions to the development of comparative literature and cinema studies in the Department of Modern French Literature. One of Patrizia Lombardo’s major fields of research has been the study of emotions in the arts and she led a large-scale project called Aesthetic Emotions and Affective Dynamics at the Swiss Center for Affective Sciences (CISA). She published numerous articles in prestigious scientific journals and was part of numerous editorial boards (Critique, Critical Quaterly, Studia UBB. Dramatica, Ekphrasis). Her publications covered vast areas: 19th century literature and culture (Stendhal, Poe, Baudelaire), cinematography, aesthetics, and the affective experience of art. Some of her extraordinary ideas and insights have been collected in the following books: Edgar Poe et la modernité (Birmingham, Alabama: Summa Publications, 1985), The Three Paradoxes of Roland Barthes (Athens: Georgia University Press, 1989), Cities, Words and Images. From Poe to Scorsese (Houndmills, Basingstoke: Palgrave Macmillan, 2003), Memory and Imagination in Film. Scorsese, Lynch, Jarmusch, Van Sant (Houndmills, Basingstoke: Palgrave Macmillan, 2014).